Relationship Between Vitamin D Deficiency and Chronic Low Back Pain in Postmenopausal Women - Rkain, Hanan; Bouaddi, Ilham; Ibrahimi, Azeddine; Lakhdar, Touria; Abouqal, Redouane; Allali, Fadoua; Hajjaj-Hassouni, Najia (Current Rheumatology Reviews, 2013)
Objective: To examine whether vitamin D deficiency is a determinant risk factor of chronic low back pain (LBP) in Moroccan postmenopausal women. Methods: A biochemical assay of serum calcium, phosphate, 25(OH)D, and parathormone (PTH) was performed for 105 patients complaining from a chronic LBP with no obvious causes and compared to those of 45 healthy patients. All participants were postmenopausal. Patients were matched with controls for age and body mass index (BMI). Vitamin D deficiency was defined as a circulating level of 25(OH)D below 20 ng/ml. Results: Vitamin D deficiency was significantly more common in patients suffering from chronic LBP than in controls (79 % vs 61.4 %; P= 0.02). Falls antecedent was also associated with chronic LBP (37.1 % in patients vs 20.5% in controls; P< 0.01). There was no significant association between chronic LBP and age, BMI, smoking status, nor with number of pregnancies. In multiple logistic regression, after adjusting for potential confounders factors potentially influencing chronic LBP (age, BMI, smoking status, number of pregnancies), the main determinants of chronic LBP were vitamin D deficiency [OR 2.5 (95% IC, 1.1-5.8; P = 0.04)] and falls antecedent [OR 3 (95% IC, 1.2-7.2; P = 0.01)]. Conclusion: Our study shows a significant association between vitamin D deficiency and chronic LBP in Moroccan postmenopausal women. Further studies are clearly warranted to determine the effectiveness and the mechanism(s) of this links between vitamin D deficiency and chronic LBP.
Keywords: women